TEACHING STRATEGIES USED BY ENGLISH TEACHERDURING PANDEMIC SITUATION AT EIGHTHGRADE OF SMP NEGERI 1 LAHUSA - Hulu, Rospinta; Zagoto, Sitasi; Laia, Restu Damai (Research on English Language Education, 2021)
Coronavirus disease (Covid-19) Pandemic has spread in many countries included Indonesia. As consequence that it was not only activities in the economic sector are limited, world of education was also restricted because of the Covid-19, so the teaching and learning activities cannot be carried out as usual. This was challenge for all of the teachers. There was changed in the teaching and learning situation, teaching and learning system, and the way of convey the material. Therefore, the objectives of this research were to describe teaching strategies used by English teacher during pandemic situation at Eighth Grade of SMP Negeri 1 Lahusa. This research was designed by applying qualitative descriptive. The instruments of data collection were observation and interview. After analyzing the data, researcher found the result. The teaching strategies used by English teacher during pandemic situation, namely: (1) teachers adjusted learning objectives to basic competencies and the students level, (2) teachers selected teaching and learning approach by having good communication and gave motivation for the students, (3) teachers adjusted teaching and learning method to the duration of time and the availability of text books, (4) teachers adjusted norm and minimal success or criteria by finding how many students are interested in the lesson and how many students are capable of learning.